Case Studies in e-Government 2.0: Changing Citizen Relationships - Boughzala, Imed (Springer, 2015)
The goal of this book is to provide a comprehensive, multi-dimensional approach to research and practice in e-government 2.0 implementation. Contributions from an international panel of experts apply a variety of methodological approaches and illustrative case studies to present state-of-the-art analysis and perspectives.